Prognostic value of clinical and Doppler echocardiographic findings in children and adolescents with significant rheumatic valvular disease - Fátima Derlene da Rocha Araújo; Eugênio Marcos Andrade Goulart; Zilda Maria Alves Meira (Annals of Pediatric Cardiology, 2012)
Introduction: The diagnosis of acute rheumatic fever (RF) is based on clinical findings. However, during the chronic phase of the disease, the clinical approach is not sufficient for the follow-up of the patients and the Doppler echocardiography is a tool for the diagnosis of cardiac involvement. Prognostic variables that influence long-term outcomes are not well known. Methods: 462 patients with RF according to Jones criteria were studied, and followed-up from the initial attack to 13.6 ± 4.6 years. All patients underwent clinical assessment and Doppler echocardiography for the detection of heart valve involvement in the acute and chronic phases. Multivariate logistic regression analysis was used to identify the factors influencing long-term heart valve disease. Results: Carditis occurred in 55.8% and subclinical valvulitis in 35.3% patients. In the chronic phase, 33% of the patients had significant valvular heart disease. No normal Doppler echocardiography exam was observed on patients who had severe valvulitis, although heart auscultation had become normal in 13% of these. In the multivariate analysis, only the severity of carditis and the mitral and/or aortic valvulitis were associated with significant valvular heart disease. Chorea or arthritis were protective factors for significant valvular heart disease, odds ratio 0.41 (95% C.I. 0.22 - 0.77) and 0.43 (95% C.I. 0.23 - 0.82), respectively. Conclusions: Our study suggests that the use of Doppler echocardiography during RF helps to identify prognostic factors regarding the development of significant valvular heart disease. Initial severe carditis is an important factor in the long-term prognosis of chronic RHD, whereas arthritis and chore during the initial episode of RF appears to be protective. Strict secondary prophylaxis should be mandatory in high risk patients.